Beyond Viral Trends: Analyzing the Impact of Service Quality, Destination Image, and Experiential Marketing on Tourist Satisfaction and Revisit Intention in West Java’s Viral Nature Destinations - Oktaviani, Desy; Latifah, Ifa; Sukma, Andhi (Technium Business and Management, 2025)
The widespread use of smartphones and social media has profoundly impacted the travel industry, transforming lesser-known destinations into viral hotspots. In West Java, platforms like Instagram and TikTok have significantly increased tourist arrivals by highlighting "viral" locations. While this has led to economic benefits, concerns about the sustainability of such rapid and unpredictable growth remain, as these destinations risk over-reliance on viral trends and face potential environmental degradation. This study examines key factors—service quality, destination image, and experiential marketing—that influence tourist satisfaction and revisit intention in West Java viral nature destinations. Using a quantitative descriptive approach, data were collected from 161 travelers and analyzed via SEM-PLS. Results show that while destination image, service quality, and experiential marketing significantly affect satisfaction, only service quality has a direct impact on revisit intention. These findings emphasize the need for long-term strategies beyond viral trends to ensure sustainable tourism growth and preserve the natural environment.